History and recent developments in divergent electrolytes towards high-efficiency lithium–sulfur batteries – a review. Issue 13 (16th June 2021) - Ponnada, Srikanth; Kiai, Maryam Sadat; Gorle, Demudu Babu; Nowduri, Annapurna
Abstract : Lithium–sulfur batteries, with a high specific capacity, low cost and environmental friendliness, could be investigated as a next-generation energy-storage system. Abstract : Lithium–sulfur batteries, with a high specific capacity, low cost and environmental friendliness, could be investigated as a next-generation energy-storage system. However, the limitations of lithium–sulfur batteries in capacity retention are directly related to the role of the electrolyte. Recently, most of the research has focused on controlling the solubility of polysulfides in the electrolyte to minimize capacity fading. A range of electrolytes with much improved charge–discharge behavior has been suggested, for example, carbonates, ethers, ionic liquids and solid polymers as solid inorganic and novel hybrid electrolytes. Understanding real interactions with these improved electrolytes could lead to performance enhancement up to the levels of reliability needed for practical applications. In fact, the successful development of the lithium–sulfur battery needs a judicious choice of modified electrolyte. Additionally, the electrolyte composition should have good compatibility with the lithium anode as well as the cathode material. This review highlights the recent research progress for lithium–sulfur batteries with various improved electrolytes, with a focus on the chemistry of polysulfides, including polysulfide solubility and its influence on battery performance.